Functional properties of the dietary fibers and their using in the manufacturing technology of fish products - T. N. Pivnenko (Пищевые системы)
This review presents the up-to-date scientific ideas about the role of dietary fibers of plant origin (fiber and hydrocolloids) and animal origin (chitosan and collagen) in the food systems. The main attention is focused on their significance and methods of their using in the manufacturing technology of fish products. Dietary fibers are considered as important components of a diet; the dietary fibers prevent certain disorders and regulate the physical and mental health of the population. Consuming of fish products contributes both to the enrichment of raw materials with functional ingredients, as well as to the increasing in the efficiency of processing of raw materials, including underestimated and underutilized aquatic biological resources. The review shows the influence of dietary fibers on the restructuring of fish muscles systems, their ability to hold water and fats, to stabilize emulsions, to change their sensory characteristics, to increase the yield of the finished food products, and also their ability to influence the shelf life of the finished food product. The mechanisms of involving the certain groups of dietary fibers into the physicochemical and biochemical processes of interaction with the components of fish raw materials are considered; the influence of various conditions of processing on gelation and emulsification is studied. The factors that provide antimicrobial and antioxidant effects of various dietary fibers are given. The properties and examples of using the commercial fiber preparations obtained from various sources are analyzed separately, and the significance of the molecular structure of chitosan and collagen for ensuring the specified technological parameters is considered. It is concluded that using the dietary fiber in the manufacturing process of fish products increases the economic efficiency of production and contributes to the development of the healthy food industry.